(untitled) (Journal of Nobel Medical College, 2025)
Background: Tuberculosis (TB) remains a major public health challenge in Nepal. Medical comorbidities can adversely impact the outcomes of TB treatment. This study aims to assess the prevalence and pattern of major medical comorbidities among newly diagnosed TB patients in Nepal. Materials and Methods: This cross-sectional study was conducted from March 2023 to April 2025 at Tribhuvan University Teaching Hospital, Nepal. Adults aged ≥18 years with newly diagnosed TB were enrolled. Patients with incomplete data, prior TB treatment, or pregnancy were excluded. Data on demographic features, smoking history, anemia status, and comorbidities, including diabetes mellitus, chronic liver disease, chronic kidney disease, ischemic heart disease, hypothyroidism, and COPD, were collected. Statistical analysis was performed using SPSS v. 25. Results: Among 140 TB patients (mean age: 48.56 years; 69% male), 80 (57%) had pulmonary TB and 60 (43%) had extrapulmonary TB. A total of 72.1% were anemic. Comorbidities were found in 40 patients: COPD (10.7%), CKD (9.3%), hypothyroidism (5.7%), CLD (3.6%), and IHD (1.4%). Comorbidities were more common in patients aged >60 years and in males. Bagmati Province had the highest proportion of cases (47.9%) and comorbidities. Conclusion: A high burden of comorbidities exists among patients diagnosed with tuberculosis in Nepal. Early detection and integrated management of these conditions are essential for optimizing TB care.